The Achievement of Literary Authority : Gender, History, and the Waverly Novels - Ferris, Ina (Cornell University Press, 2019)
Although literary historians have largely neglected them, Sir Walter Scott's Waverley Novels mark a pivotal moment in the formation of the modern literary field, Ina Ferris argues, exemplifying the complex intersections of gender and genre in the evolution of nineteenth-century literary authority. Focusing on the critical reception of Scott's early works, Ferris shows how their extraordinary success propelled the novel from the margins of the culture into the literary hierarchy. Drawing on the insights of poststructuralist, feminist, and Bakhtinian theory, Ferris reconstructs reviewers' debates about fiction at several critical points in Scott's career. His literary authority and innovative power, she maintains, depended on the way in which his historical novels responded to the anxieties about discourse and modernity expressed in the literary reviews. Gender was a central source of anxiety, and the "manliness" of Scott's historical novels was decisive in their legitimation of the novel. It was largely through a problematic allegiance to the "female" genre of romance, however, that the Waverley Novels both recuperated fiction for male reading and helped to redefine for the nineteenth century the writing of history itself. Ferris locates the Waverley Novels in relation to fiction and history by such contemporaries of Scott's as Maria Edgeworth, Lady Morgan, John Galt, James Hogg, Augustin Thierry, and Thomas Babington Macaulay. Students of the novel, feminist critics, and others interested in the relations between history and fiction will want to read The Achievement of Literary Authority.